Palmitic Acid-Stearic Acid/Expanded Graphite as Form-Stable Composite Phase-Change Material for Latent Heat Thermal Energy Storage. (21st March 2020) - Zhou, Dongyi; Zhou, Yuhong; Yuan, Jiawei; Liu, Yicai
Abstract : The aim of this study is to prepare a novel form-stable phase-change material (PCM), palmitic acid-stearic acid/expanded graphite (PA-SA/EG) PCM, for latent heat thermal energy. A eutectic mixture of palmitic acid and stearic acid is incorporated with expanded graphite (EG). The thermal properties and microstructure of the novel PCMs were studied. The optimal mass ratio of PA-SA in composite PCM is approximately 92.8%. DSC results showed that the novel PCMs had suitable phase-change temperature (T m : 55.18°C, T f : 54.91°C) and high latent heat (H m : 176.2 J/g, H f : 175.6 J/g), and good thermal performance was maintained after 1500 times thermal cycling. The PA-SA binary eutectic mixture was uniformly distributed in the porous structure of EG, and the PCM did not leak even in molten state. EG had little effect on the thermal properties of the PA-SA binary eutectic mixture and remarkably improved the thermal conductivity of the composite PCMs. TGA test indicated that the composite PCM had nice thermostability in the range of operating temperature. Based on all these results, the PA-SA/EG composite PCM is a promising material for low-temperature thermal energy storage applications.